1995
DOI: 10.1128/aem.61.4.1194-1200.1995
|View full text |Cite
|
Sign up to set email alerts
|

Diversity among Field Populations of Bradyrhizobium japonicum in Poland

Abstract: Genetic structure in field populations of Bradyrhizobium japonicum isolated in Poland was determined by using several complementary techniques. Of the 10 field sites examined, only 4 contained populations of indigenous B. japonicum strains. The Polish bradyrhizobia were divided into at least two major groups on the basis of protein profiles on polyacrylamide gels, serological reaction with polyclonal antisera, repetitive extragenic palindromic PCR fingerprints of genomic DNA, and Southern hybridization analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
2
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 35 publications
3
15
2
3
Order By: Relevance
“…Furthermore, these German indigenous rhizobia are distributed in fields with soybean cultivation histories, which indicates that the natural population of rhizobia have been affected by both the cultivation of different legume crops and the application of inoculants. These results are supported by other investigations in Europe, such as Poland and Spain, and also in Africa (Madrzak et al, 1995;Bourebaba et al, 2016;Chibeba et al, 2017).…”
Section: Phylogenetic Properties Of Isolatessupporting
confidence: 89%
“…Furthermore, these German indigenous rhizobia are distributed in fields with soybean cultivation histories, which indicates that the natural population of rhizobia have been affected by both the cultivation of different legume crops and the application of inoculants. These results are supported by other investigations in Europe, such as Poland and Spain, and also in Africa (Madrzak et al, 1995;Bourebaba et al, 2016;Chibeba et al, 2017).…”
Section: Phylogenetic Properties Of Isolatessupporting
confidence: 89%
“…Indeed, all isolates of cluster III and most of those of cluster I which tolerate 1AE5% NaCl and higher concentrations were isolated from saline soils. Regarding the intrinsic resistance to antibiotics, it has been reported that fast-growing strains are more sensitive to antibiotics (Jordan 1984) than slow-growing rhizobia (Madrzak et al 1995). Conversely, in our study, chickpea rhizobial strains which are a mixture of fast, slow and extra-slow growers, showed a wide range of behaviour with regard to antibiotics and heavy metals.…”
Section: Discussioncontrasting
confidence: 53%
“…Our data did not support either of these alternatives. The diversity that we have found in the population studied was higher than the diversity found in other studies (3,4,6,12,14,15,20). As any individual method detects only a fraction of the total strains in a population (24) and the strains recovered from nodules may be only a fraction of soil population (5), the number of different Adenocarpus-nodulating strains in the Tenerife forest could be enormous.…”
Section: Study Of a Natural Population: A Real Application Of The Metcontrasting
confidence: 55%